O verbo-visual como estratégia discursiva nos infográficos: uma análise da seção Gráfico do Nexo Jornal - Montargil, Gilmar da Silva (2020)
The infographic is a multimodal genre mobilized in different discursive practices in hypermodernity, especially in regard to the journalistic sphere. In this sense, in order to facilitate the process of meaning making in cyberculture, infographics are used as tool for explaining phenomena, studies and data. Therefore, this qualitative-interpretative research aims to analyze the discursive strategies that are articulated in the production of the infographic genre explored in Nexo Jornal. Being that, this study was anchored to the dialogic language conception studies of discursive genres proposed by the Circle of Bakhtin. For this reason, the aspects of theme, composition, style, circulation spheres, supports and languages were studied. With the hypothesis that the strategies used in the infographics of Nexo Jornal became, over time, more hybrid to potentiate / amplify effects of meaning, the corpus of analysis consists of 16 infographics from Graph Section of the Nexo Jornal and covers a diachronic line. From 2015 to 2019, these materials were selected every quarter. Based on the salient characteristics identified in the corpus and the theoretical framework, we constitute an analysis protocol with a view to discursive, transmutatory and sociosemiotic aspects based on Kress and Van Leeuwen (2001 [1996]), Kress (2001, 2005a, 2005b) and Cope and Kalantzis (2009a, 2009b, 2015). In addition to the theoretical framework: Bakhtin (1997, 2015, 2016), Volochinov (2013), Brait (2013), Rodrigues (2005), Rojo (2013), Charaudeau (2013), Jenkins (2011) Spinillo and Escobar (2016) and Rajamanickam (2005). The results of the analysis revealed that the effects of meanings produced result from the newspaper’s editorial choices in articulation with the compositional arrangement that privileges the linking of genres and the mixture of different visual resources. However, the development of this articulation is not constant, as it is based on textual writing blocks, instead of more complex and hybrid infographics.